The diabolical proof (probatio diabolica) in flagrante delicto arrest (Revista do Tribunal Regional Federal da 3ª Região, 2025)
This article seeks to examine the issue of probatio diabolica (diabolical or negative proof), particularly in cases of flagrante delicto arrest, focusing on the rights of the detained person. To this end, it initially presents the concept of probatio diabolica, defined as evidence that is virtually impossible or unfeasible for the party asserting the fact to produce. Next, it discusses the characterization of this type of evidence within police investigations and in the context of flagrante delicto arrests. Subsequently, the legal analysis focuses on the evaluation of evidence in police proceedings, specifically involving the rights of individuals arrested in flagrante when, in order to rule out involvement in the illegal act, they indicate a negative fact that is practically impossible to prove. This scenario highlights a structural inequality in access to justice, since, in many cases, the burden of proving the absence of involvement in the crime is imposed on the suspect, disregarding the hurdles faced by the arrested individuals, notably in contexts of socioeconomic vulnerability. The methodology of this research involves a qualitative, bibliographic, and documentary review, incorporating an analysis of criminal cases where probatio diabolica was evaluated, a study of pertinent regulatory legislation and criminal procedural jurisprudence, along with participant observation with police chief delegates. It can be concluded that, in order to decide on a flagrante delicto arrest in accordance with Brazilian law, the Police Chief Delegate must consider and investigate the diabolical or negative evidence indicated by crime suspects, utilizing state police resources to verify the account and facts presented by the person arrested, while upholding the rights of the arrested individual and aiming to clarify the offense during the police investigation.
Keywords: police inquiry; probatio diabolica; flagrante delicto arrest; burden of proof; rights of the detained person